Challenges and Innovations in a Community-Based Participatory Randomized Controlled Trial. (February 2017) - Goodkind, Jessica R.; Amer, Suha; Christian, Charlisa; Hess, Julia Meredith; Bybee, Deborah; Isakson, Brian L.; Baca, Brandon; Ndayisenga, Martin; Greene, R. Neil; Shantzek, Cece
Randomized controlled trials (RCTs) are a long-standing and important design for conducting rigorous tests of the effectiveness of health interventions. However, many questions have been raised about the external validity of RCTs, their utility in explicating mechanisms of intervention and participants' intervention experiences, and their feasibility and acceptability. In the current mixed-methods study, academic and community partners developed and implemented an RCT to test the effectiveness of a collaboratively developed community-based advocacy, learning, and social support intervention. The goals of the intervention were to address social determinants of health and build trust and connections with other mental health services in order to reduce mental health disparities among Afghan, Great Lakes Region African, and Iraqi refugee adults and to engage and retain refugees in trauma-focused treatment, if needed. Two cohorts completed the intervention between 2013 and 2015. Ninety-three adult refugees were randomly assigned to intervention or control group and completed four research interviews (pre-, mid-, and postintervention, and follow-up). Several challenges to conducting a community-based RCT emerged, including issues related to interviewer intervention to assist participants in the control group, diffusion of intervention resources throughout the small refugee communities, and staff and community concerns about the RCT design and what evidence is meaningful to demonstrate intervention effectiveness. These findings highlight important epistemological, methodological, and ethical challenges that should be considered when conducting community-based RCTs and interpreting results from them. In addition, several innovations were developed to address these challenges, which may be useful for other community–academic partnerships engaged in RCTs.